Synthesis of Co doped ZnWO4 for simultaneous oxidation of RhB and reduction of Cr(VI) under UV-light irradiation. Issue 4 (August 2018) - Alam, Umair; Khan, Azam; Bahnemann, Detlef; Muneer, M.
Graphical abstract: Simultaneous removal of RhB and Cr(VI) in the presence of Co doped ZnWO4 nanorod under UV light source. Highlights: Co doped ZnWO4 nanorod was synthesized by surfactant free hydrothermal method. Degradation of RhB, MO, MB and reduction of Cr(VI) conducted under UV light source. 1% Co-ZW exhibits excellent activity in the oxidation and reduction reactions. The species involved in the degradation reaction has been determined. The reaction mechanism of Co doped ZnWO4 has been discussed and proposed. Abstract: In this study, one-step hydrothermal route was adopted to synthesize Co doped ZnWO4 nanorods for efficient removal of inorganic and organic pollutants. The samples were carefully characterized by standard analytical techniques to investigate the optical, morphological and structural properties of the prepared samples. TEM analysis shows the rod-like morphology with average diameter of 60–100 nm. The activity of prepared samples was evaluated by studying the photodegradation of RhB, MB, MO, photo-reduction of Cr(VI) and simultaneous photo-oxidation and reduction of binary mixture of RhB and Cr(VI) under UV-light source. Among the series of prepared samples, 1 mol% Co doped ZnWO4 (1 Co-ZW) showed improved photocatalytic activity in both single and mixed pollutant solutions. In the single dye solutions, a maximum degradation of 94.4%, 95% and 86.4% was obtained for RhB, MB and MO, respectively under 120 min of irradiation using 1 Co-ZW. Moreover, a maximum efficiency of 97.8% and 99% was achieved by 1 Co-ZW for the oxidation of RhB and reduction of Cr(VI), respectively from the binary (RhB + Cr(VI)) solution under the same irradiation time. The degradation results indicate that simultaneous degradation of pollutants is more prominent than that of the individual ones. The reactive species involved in the removal of RhB and Cr(VI) was determined by different scavengers and a probable mechanism for enhanced photocatalytic activity has been proposed accordingly. The present work offers an innovative approach towards the design and development of reusable catalysts to remove both organic and inorganic pollutants present in wastewater using UV-light source.